2002
DOI: 10.2527/2002.8061433x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zeranol or melengestrol acetate (MGA) on testicular and antler development and aggression in farmed fallow bucks

Abstract: Fifteen yearling fallow bucks were randomly assigned by BW to one of three treatment groups: control (C; n = 5), melengestrol acetate (MGA; n = 5), and zeranol (Z; n = 5), to evaluate effects on testicular development, aggressive behavior, antler growth, sexual activity, ADG, and BW. Zeranol-treated bucks received zeranol ear implants (36 mg) at 90-d intervals, and MGA-treated bucks received MGA in the ration (100 microg x animal(-1) x d(-1)). Bucks grazed ryegrass/Coastal bermudagrass pasture and were supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Our results demonstrate that male fringe-eared oryx fed MGA had reduced fecal androgens associated with a concomitant decline in all forms of agonistic behavior, including both ritualized and escalated aggression. Although other studies have suggested such an effect of MGA on ungulate species [Stover et al, 1987;Blumer et al, 1992;Wilson et al, 2000], this study is the first to quantitatively document the drug's behavioral effects on aggression. In this light it is interesting to note that the effects appear to mediate aggression at all levels, ranging from symbolic posturing to escalated and injurious contact, suggesting specific motivational effects, rather than a general effect on activity level.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Our results demonstrate that male fringe-eared oryx fed MGA had reduced fecal androgens associated with a concomitant decline in all forms of agonistic behavior, including both ritualized and escalated aggression. Although other studies have suggested such an effect of MGA on ungulate species [Stover et al, 1987;Blumer et al, 1992;Wilson et al, 2000], this study is the first to quantitatively document the drug's behavioral effects on aggression. In this light it is interesting to note that the effects appear to mediate aggression at all levels, ranging from symbolic posturing to escalated and injurious contact, suggesting specific motivational effects, rather than a general effect on activity level.…”
Section: Discussionmentioning
confidence: 78%
“…The concentration of MGA the oryx received was determined on the basis of previous studies in which effective contraception was achieved for a variety of species [Raphael et al, 1992;Patton et al, 2000]. A lower dose (0.1 mg/head/day) appeared to decrease aggression in farmed fallow bucks but no decrease in sperm production when compared to controls [Wilson et al, 2000]. As in fallow bucks, when muntjac (Muntiacus reevesi) were treated with MGA (0.02-0.3 mg/day), casual observation of behavior indicated reduced aggression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with deer have demonstrated some success in suppression of male reproductive activity with synthetic progestagens such as melengestrol acetate (fallow deer Dama dama, Wilson et al 2002) and medroxy progesterone acetate (red deer, Muir et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Melengestrol acetate (MGA) has been used widely in domestic cattle to reduce aggressive behavior that might ultimately impact meat quality [Imwalle et al, 2002]. MGA also has been used in farmed fallow deer [Wilson et al, 2002] and the fringe-eared oryx [Patton et al, 2001] to effect aggression control. The aim of this study was to investigate the effects of MPA and MGA on gerenuk serum testosterone concentrations, semen production and agonistic behavior, and to monitor the health of treated animals.…”
Section: Introductionmentioning
confidence: 99%